Possibility studies of using local cement in oil and gas wells cementing operations in Malaysia - Shahrudin, Shahrin; Samsuri, Ariffin; Suhaimi, Ahmad; Nasir, Abu Samah; Ahmad, Zainuddin (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)
Portland cement, which is primal a construction material, is used extensively in oil and gas wells. To justify its ability to be used in the oil well cementing operations, Portland cement must comply with the standards set by the American Petroleum Institute (API) in terms of their chemistry and physical properties requirements. Therefore, to determine the suitability of our locally produced Portland cement and pulverize fly ash cement: compressive strength, thickening time, fluid loss and free water test were carried out closely followed the API Specification 10. Generally, locally produced cement proved to comply to the API Specification and has the possibility to be used in cementing operations.